The association between repeated abortions during childbearing age and the psychological well-being of postmenopausal women in Southwest China: an observational study - Xu Li; Anjiao Peng; Lin Li; Lei Chen (BMC, 2024)
Abstract Background The issue of whether abortion increases the risk of future mental health problems for women remains a debated topic, and there is a lack of evidence from large-scale studies conducted in China. This study aimed to investigate the potential associations between abortions, particularly repeated abortions, and the mental health status of postmenopausal women in Southwest China. Methods The data were obtained from the baseline survey of a multi-center natural population cohort study in cooperated with medical consortia in Southwest China. A standard structured questionnaire was used to assess abortion status among women of childbearing age. The 7-item Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9) were used to evaluate psychological well-being. Subsequently, multiple logistic regression analysis was employed to examine the associations between the quantity and reasons for abortions and the mental health status of postmenopausal women. Results A total of 9991 postmenopausal women were enrolled (mean age: 60.51 years), of whom 11.09% (1108 individuals) reported mental health problems (5.54% for depression and 8.27% for anxiety). Multiple logistic regression analysis revealed that, compared with women without any history of abortion, postmenopausal women who reported three or more abortions during their childbearing years were likely to have worse mental health conditions (OR [95% CI]: 1.37 [1.13, 1.67]). Additionally, women who reported a history of abortions for socio-economic reasons were also correlated with an increased risk of mental health issues after menopause (OR [95% CI]: 1.34 [1.08, 1.66]). Conclusions Women who reported a history of three or more abortions were at an increased risk of experiencing mental health issues after menopause. Reproductive-age women should enhance their contraceptive awareness to prevent unintended pregnancies and subsequent abortions. Healthcare institutions are recommended to strengthen psychological counseling for women who have undergone abortions.